Traces of Islamic Education and Archipelago Culture Research in Indonesia and Brunei Darussalam: A Bibliometric Analysis - Marlina, Reni (Proceedings: International Seminar On Educational Studies, 2025)
This study aims to analyze the dynamics and research trends of Islamic education and Nusantara culture in Indonesia and Brunei Darussalam using a bibliometric approach. The focus of the analysis is to identify patterns of collaboration, thematic evolution, and research gaps within the international literature. Data were obtained from the Scopus database covering publications from 2013 to 2023 and analyzed using VOSviewer version 1.6.20. The analysis employed four main indicators: co-authorship, co-occurrence of keywords, overlay visualization, and density visualization. The results reveal five main clusters representing research foci, namely Islamic education, Malay civilization, cultural heritage, Islamic leadership, and digital learning. Temporal trends indicate a paradigm shift from normative studies such as religious values to contemporary issues including digital Islamic learning and heritage management. Furthermore, the density mapping highlights Islamic education as the central domain connecting various related themes. These findings demonstrate that Islamic education plays a strategic role in preserving Malay cultural identity and shaping Islamic civilization in Southeast Asia. The study recommends strengthening international academic collaboration and expanding research in digital Islamic education and comparative studies as future directions for knowledge development.